P110α-mediated constitutive PI3K signaling limits the efficacy of p110δ-selective inhibition in mantle cell lymphoma, particularly with multiple relapse - Iyengar, Sunil (American Society of Hematology, 2013)
Phosphoinositide-3 kinase (PI3K) pathway activation contributes to mantle cell lymphoma (MCL) pathogenesis, but early-phase studies of the PI3K p110δ inhibitor GS-1101 have reported inferior responses in MCL compared with other non-Hodgkin lymphomas. Because the relative importance of the class IA PI3K isoforms p110α, p110β, and p110δ in MCL is not clear, we studied expression of these isoforms and assessed their contribution to PI3K signaling in this disease. We found that although p110δ was highly expressed in MCL, p110α showed wide variation and expression increased significantly with relapse. Loss of phosphatase and tensin homolog expression was found in 16% (22/138) of cases, whereas PIK3CA and PIK3R1 mutations were absent. Although p110δ inhibition was sufficient to block B-cell receptor–mediated PI3K activation, combined p110α and p110δ inhibition was necessary to abolish constitutive PI3K activation. In addition, GDC-0941, a predominantly p110α/δ inhibitor, was significantly more active compared with GS-1101 against MCL cell lines and primary samples. We found that a high PIK3CA/PIK3CD ratio identified a subset of primary MCLs resistant to GS-1101 and this ratio increased significantly with relapse. These findings support the use of dual p110α/p110δ inhibitors in MCL and suggest a role for p110α in disease progression.